2011
DOI: 10.1111/j.1442-2050.2011.01272.x
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient patterns and risk of esophageal squamous cell carcinoma: a case-control study

Abstract: Although Iran is a high-risk country for esophageal squamous cell carcinoma (ESCC), the contribution of overall nutrient intakes to this high incidence rate is not yet clear. The aim of this study was to examine the association between nutrient patterns and risk of ESCC in Iran. Forty-seven patients with ESCC and 96 frequency-matched hospital controls underwent private interviews, and dietary habits were collected using a validated food-frequency questionnaire. Factor analysis was conducted and two major nutri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 44 publications
0
22
1
1
Order By: Relevance
“…The risk estimates with corresponding 95% confidence intervals (95% CIs) were reported. In the end, nine eligible articles (case–control design) (Bahmanyar and Ye, 2006; De Stefani et al , 2008a, 2008b, 2009; Hajizadeh et al , 2010, 2012; Navarro Silvera et al , 2011; Ibiebele et al , 2012; Bravi et al , 2012b) containing 1464 cases and 7863 controls were identified through a full text examination of 265 potential publications. Figure 1 shows a flow chart of literature search.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The risk estimates with corresponding 95% confidence intervals (95% CIs) were reported. In the end, nine eligible articles (case–control design) (Bahmanyar and Ye, 2006; De Stefani et al , 2008a, 2008b, 2009; Hajizadeh et al , 2010, 2012; Navarro Silvera et al , 2011; Ibiebele et al , 2012; Bravi et al , 2012b) containing 1464 cases and 7863 controls were identified through a full text examination of 265 potential publications. Figure 1 shows a flow chart of literature search.…”
Section: Methodsmentioning
confidence: 99%
“…Figure 1 shows a flow chart of literature search. Three articles (De Stefani et al , 2008a, 2008b, 2009) came from a study in Uruguay and two articles (Hajizadeh et al , 2010, 2012) from a study in Iran were treated as five different studies, because the articles from a same study reported different dietary patterns: the three articles from the Uruguay study reported three nutrient patterns (high fat, carbohydrates, and antioxidants) in men and women (De Stefani et al , 2008a), four food patterns (traditional, healthy, high fat, and drinker) in men and women (De Stefani et al , 2008b), and four food patterns (prudent, traditional, western, and drinker) in men (De Stefani et al , 2009), respectively; the two articles from the Iran study reported two nutrient patterns (factor 1 and factor 2) (Hajizadeh et al , 2012) and two food patterns (healthy diet and western diet) (Hajizadeh et al , 2010), respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, another case-control study performed in Iranian middle aged to elderly adults used factor analysis to investigate nutrients and dietary patterns associated with ESCC. Two dietary nutrient patterns were identifi ed and factor 2, but not factor 1, had an inverse relationship with ESCC risk (Hajizadeh et al 2012 ). Interestingly, dietary folate and vitamin B 6 were loaded in factor 1 which saw no effect whereas vitamin B 12 was loaded in factor 2 which was protective.…”
Section: Esophageal Cancermentioning
confidence: 97%
“…Results indicated that the administered questionnaire was of reasonable relative validity and reproducibility for assessment of dietary intake in Tehranian adults [16,17]. This questionnaire has been used before by Hajizadeh et al to study dietary patterns in relation to general obesity and central adiposity among Iranian women [18].…”
Section: Dietary Assessmentmentioning
confidence: 99%